2016
DOI: 10.3390/info7020019
|View full text |Cite
|
Sign up to set email alerts
|

Minimax Duality for MIMO Interference Networks

Abstract: Abstract:A minimax duality for a Gaussian mutual information expression was introduced by Yu. An interesting observation is the relationship between cost constraints on the transmit covariances and noise covariances in the dual problem via Lagrangian multipliers. We introduce a minimax duality for general MIMO interference networks, where noise and transmit covariances are optimized subject to linear conic constraints. We observe a fully symmetric relationship between the solutions of both networks, where the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The feasible set of the worst-case noise minimization contains as the only element, i.e., the noise statistics are fixed. However, the formulation as a minimax problem enables us to apply the minimax uplink-downlink duality from [56], [57]. This duality was shown in [56] for proper complex signals, but by repeating the derivation from [56] for real-valued systems, we obtain that the above optimization has the same optimal value as the following composite real minimax uplink problem.…”
Section: Optimality Of Proper Signaling In Gaussian Mimo Broadcastmentioning
confidence: 84%
See 2 more Smart Citations
“…The feasible set of the worst-case noise minimization contains as the only element, i.e., the noise statistics are fixed. However, the formulation as a minimax problem enables us to apply the minimax uplink-downlink duality from [56], [57]. This duality was shown in [56] for proper complex signals, but by repeating the derivation from [56] for real-valued systems, we obtain that the above optimization has the same optimal value as the following composite real minimax uplink problem.…”
Section: Optimality Of Proper Signaling In Gaussian Mimo Broadcastmentioning
confidence: 84%
“…However, until recently, it had not been shown that the optimality of proper signals also holds under a shaping constraint, i.e., a constraint on the sum transmit covariance matrix instead of on the sum power. 7 In our recent works [34], [35], we used the minimax duality with linear conic constraints from [56], [57] in combination with a power shaping matrix and an impropriety matrix to show this more general result. As discussed in Section III.D, these matrices fit into the framework proposed in this paper.…”
Section: Optimality Of Proper Signaling In Gaussian Mimo Broadcastmentioning
confidence: 99%
See 1 more Smart Citation
“…[19]). Since (18) was shown to have zero duality gap for C ≻ 0 [30], we can consider the Lagrangian dual problem of the maximization in ( 16) and express R ⋆ A (C) as…”
Section: Approximation and Primal Decompositionmentioning
confidence: 99%
“…The proposed algorithm aims at maximizing the tolerable interference power, but without exploiting the cross-CSI. A more general scenario is considered in [29], where an uplinkdownlink duality is introduced for minimax problems with linear matrix inequality constraints, which usually appear in robust optimization under worst-case interference.…”
Section: Introductionmentioning
confidence: 99%